2008
DOI: 10.1073/pnas.0806619105
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammation and autoimmunity caused by a SHP1 mutation depend on IL-1, MyD88, and a microbial trigger

Abstract: A recessive phenotype called spin (spontaneous inflammation) was induced by N -ethyl- N -nitrosourea (ENU) mutagenesis in C57BL/6J mice. Homozygotes display chronic inflammatory lesions affecting the feet, salivary glands and lungs, and antichromatin antibodies. They are immunocompetent and show enhanced resistance to infection by Listeria monocytogenes . TLR-induced TNF and IL-1 production are normal in macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(133 citation statements)
references
References 35 publications
6
127
0
Order By: Relevance
“…Motheaten, viable motheaten, and spin mouse strains bearing loss of function mutations in the SHP-1 encoding gene (34,35) exhibit granulocyte and macrophage hyper-responsiveness to cytokines (36) and development of severe autoinflammatory disease (35,37). Moreover, partial SHP-1 deficiency leads to severe autoimmune disease, which develops even in the absence of B-and T-lymphocytes but is dependent on signaling via innate immune receptors, such as IL-1 and Toll-like receptors (35,37). Most likely, cells of the myeloid lineage induce the chronic inflammation observed in SHP-1 insufficient animals.…”
Section: Discussionmentioning
confidence: 99%
“…Motheaten, viable motheaten, and spin mouse strains bearing loss of function mutations in the SHP-1 encoding gene (34,35) exhibit granulocyte and macrophage hyper-responsiveness to cytokines (36) and development of severe autoinflammatory disease (35,37). Moreover, partial SHP-1 deficiency leads to severe autoimmune disease, which develops even in the absence of B-and T-lymphocytes but is dependent on signaling via innate immune receptors, such as IL-1 and Toll-like receptors (35,37). Most likely, cells of the myeloid lineage induce the chronic inflammation observed in SHP-1 insufficient animals.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our initial experiments with NFκB, treatment with ISO also resulted in the down-regulation of ATF-2, Il1r1 and Tnfrsf1b, along with the modest up-regulation of Ripk2. ATF-2, which is known to interact with c-jun, is a transcription factor primarily regulated by the stress activated MAPKs JNK and p38 and is known to play a role in the hypertrophic response [19], while Il1r1 is mainly involved in the immune and inflammatory response, through its interaction with Myd88, although it also plays a role in the activation of NFκB [20]. Tnfrsf1b plays a role in the activation of NFκB, but only in the absence of Rip proteins like Ripk2 [21].…”
Section: Targets Of β-Adrenergic Transcriptional Responses In Isolatementioning
confidence: 99%
“…Moreover, at this stage hyperinsulinemic larvae appeared to be immunosuppressed at the transcriptional level, whereas the only immune modulator showing an increased expression was ptpn6. In mammals and zebrafish, ptpn6 has been reported to be a negative regulator of the immune response (Zhang et al 2000, Tsui et al 2006, Pao et al 2007, Croker et al 2008, Lorenz 2009, Kanwal et al 2013) and a key determinant of development of insulin resistance and nonalcoholic fatty liver diseases (Xu et al 2012(Xu et al , 2014a. We found that knocking down of ptpn6 interfered with the inhibitory effect observed on key transcription factors and signal mediators of the NF-kB pathway as well as on various cytokines in larvae that had received injections of insulin.…”
Section: Discussionmentioning
confidence: 81%
“…This gene is a well-known immune modulator playing a critical role as a negative regulator of the immune response , Croker et al 2008. Importantly, PTPN6 has been described as a modulator of insulin signaling (Dubois et al 2006), and recent findings have demonstrated its importance in the development of insulin resistance and non-alcoholic fatty liver diseases in diet-induced obesity (Xu et al 2014a,b).…”
Section: Knockdown Of Ptpn6 Prevents the Downregulation Of Insulin Anmentioning
confidence: 99%
See 1 more Smart Citation